Copyright law awareness and compliance in selected university libraries in Metro Manila - De la Rosa, Felicitas G.; Faderon, Rosalie B.; Santos, Antonio M.; Gonzales, Ma. Rowena R. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2000)
The study was an attempt to determine the level of copyright law awareness of eight chief librarians and ninety section heads and unit head librarians in ten selected university libraries in Metro Manila. It also tried to determine whether or not the various libraries comply with the copyright law.
Through a survey, policies implemented to prevent copyright violations, and efforts aimed at copyright promotions among library staff and users were identified. Moreover, the copyright problems librarians usually encounter and the solutions they adopt to address them were likewise identified. Lastly, the investigation solicited the respondents' opinions regarding the effective ways of enforcing the copyright law in the Philippine libraries.
Results of the copyright awareness test showed that the respondent librarians were either moderately aware (35 percent) or highly aware (37.8 percent) of the provisions of the law. Among the ten libraries, (30 percent) had written copyright policies, (25 percent) had oral, while (42 percent) had neither of the two policies.
Despite the admission of many libraries that they have no policies promoting copyright, a number of them do other copyright promotion in their libraries through student orientations and posting of notices on all copying machines within the library premises. The libraries also encourage their staff to attend seminars and training programs on the copyright law. In addition to discussing the copyright problems they encounter in their work place, they also give their library users information through write-ups and pamphlets about the said law.
Among the copyright problems most frequently encountered by the libraries are: student request for reproduction of a textbook to avoid purchase of an expensive original copy; request to photocopy a portion of a thesis without the author's permission; and request to photocopy an entire book by a researcher from another institution.
The findings of the study indicated that awareness and knowledge of the copyright law is necessary to enable librarians to fully comply with the law. Similarly, intensive awareness campaign among library users is also a must. Other recommendations of the study include: (1) formulation of specific copyright rules; (2) discussion of pertinent provisions of the law during orientations; (3) posting of copyright signs on all copying machines within the library; (4)payment of royalties due to copyright owners; (5) formulation of guidelines on fair use; (6) establishment of an Intellectual Property Office in the University; (7) discussion of copyright policies during seminars and conferences attended by librarians.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Academic libraries--Philippines--Manila Metropolitan Area; Copyright--Philippines.